Security orchestration, automation and response for security analysts : learn the secrets of SOAR to improve MTTA and MTTR and strengthen your security posture /: learn the secrets of SOAR to improve MTTA and MTTR and strengthen your security posture. (2023) - Kovacevic, Benjamin
No abstract available